Redo aortic surgery: Does one versus multiple affect outcomes?Central MessagePerspective - Elizabeth L. Norton, MD; Kanika Kalra, MD; Bradley G. Leshnower, MD; Jane W. Wei, MPH; Jose N. Binongo, PhD; Edward P. Chen, MD (JTCVS Open, 2023)
Objective: Redo aortic surgery has a higher risk of morbidity and mortality because it is technically complex due to mediastinal adhesions, infection, and previously implanted prostheses. In this study, we sought to benchmark our single-center experience comparing outcomes in patients undergoing aortic surgery after 1 versus multiple previous cardiac operations. Methods: Between 2004 and 2019, 429 patients underwent redo aortic surgery. They were classified as aortic surgery after 1 previous surgery (first redo surgery, n = 360) and aortic surgery after 2 or more (multiple) previous surgeries (multiple redo surgery, n = 69). Postoperative outcomes and long-term survival were compared, and risk factors for mortality were identified. Results: Thirty-day mortality was lower in first redo surgery compared with multiple redo surgery (12.3% vs 21.7%, P = .03). Age, cardiopulmonary bypass time, intra-aortic balloon pump use, postoperative cerebrovascular accident, absence of postoperative atrial fibrillation, intra-aortic balloon pump, and multiple redo surgery were independent predictors of 30-day mortality. Long-term survival was similar at 15 years. Patients who received first redo surgery were older (57.9 ± 14.0 years vs 50.3 ± 15.8 years, P = .0001) and had a higher incidence of hypertension (84.7% vs 73.9%, P = .02), whereas patients who received multiple redo surgery had a higher incidence of cerebrovascular disease (31.9% vs 20.3%, P = .03). Aortic valve replacement was the most common previous operation with higher incidence in multiple redo surgery. Incidence of previous aortic surgery was similar. Cardiopulmonary bypass (246 ± 67.3 minutes vs 219.9 ± 57.5 minutes, P = .009) and crossclamp times (208.2 ± 51.8 vs 181.9 ± 50.8 minutes, P = .004) were longer in multiple redo surgery. Incidence of reentry injury and balloon pump insertion were similar. Extracorporeal membrane oxygenation use was higher in multiple redo surgery. Postoperative complications occurred at similar rates, except for higher incidence of dialysis in multiple redo surgery (14.5% vs 7.2%, P = .04). Conclusions: Multiple redo aortic procedures have a higher morbidity and mortality compared with first redo aortic procedures, with linearly increasing short-term mortality risk but similar long-term survival with the number of redo procedures.